Hábitos alimentarios de los estudiantes del programa de enfermería de la UAN en Bogotá en tiempos de pandemia (2021)
Introduction: The COVID-19 pandemic has brought many changes in habits at the population level since it was declared by the World Health Organization on March 11, 2020. Among the factors that have influenced these changes are periods of confinement, border closures, mobility restrictions, unemployment, change in study modality, social distancing, economic damage, among others. The objective of this research is to design a nursing intervention proposal to improve eating habits of university nursing students at the Antonio Nariño University. Materials and methods: A cross-sectional descriptive study was carried out, calculating the sample in a stratified manner, electronic collection of information through an adapted questionnaire that includes sociodemographic data and eating habits, developed by Barrera. Results: It is found that almost 65% of the students are in an adequate nutritional state, followed by those with overweight (31%); additionally, second semester students are the ones with the best nutritional status; more than 50% estimate that they have gained an average of 6 kilograms in weight; More than 75% of the participants consider that their eating habits have changed, especially due to changes in family income, feeding time or health problems, to a lesser extent. Conclusions: There are many changes in the eating habits of students and it can be concluded that the situation has worsened, especially due to increased sedentary lifestyle, changes associated with restrictions and social determinants of health that are mostly beyond the control of the population.